Bacillus megaterium mediated mineralization of calcium carbonate as biogenic surface treatment of green building materials - Dhami, N.; Reddy, M.; Mukherjee, Abhijit (Springer Netherlands, 2013)
Microbially induced calcium carbonate precipitation is a biomineralization process that has various applications in remediation and restoration of range of building materials. In the present study, calcifying bacteria, Bacillus megaterium SS3 isolated from calcareous soil was applied as biosealant to enhance the durability of low energy, green building materials (soil-cement blocks). This bacterial isolate produced high amounts of urease, carbonic anhydrase, extra polymeric substances and biofilm. The calcium carbonate polymorphs produced by B. megaterium SS3 were analyzed by scanning electron microscopy, confocal laser scanning microscopy, X-ray diffraction and Fourier transmission infra red spectroscopy. These results suggested that calcite is the most predominant carbonate formed by this bacteria followed by vaterite. Application of B. megaterium SS3 as biogenic surface treatment led to 40 % decrease in water absorption, 31 % decrease in porosity and 18 % increase in compressive strength of low energy building materials. From the present investigation, it is clear that surface treatment of building materials by B. megaterium SS3 is very effective and eco friendly way of biodeposition of coherent carbonates that enhances the durability of building materials.